University-Public Partnerships for Disaster Recovery: Promoting Community Resilience Through Research, Teaching, and Engagement - Gavin P. Smith; Mai T. Nguyen (The University of Alabama, 2022)
This article describes a state-supported, multiuniversity, interdisciplinary effort to address unmet disaster recovery needs identified by six hard-hit, low-capacity North Carolina communities following Hurricane Matthew. At the request of the director of the North Carolina Division of Emergency Management and the state governor, university officials created a team of faculty, practitioners, and students called the Hurricane Matthew Disaster Recovery and Resilience Initiative (HMDRRI). This 2-year program delivered research, teaching, and engagement activities of the sort that are not typically undertaken by federal or state emergency management agencies, insurance providers, or nonprofit organizations. HMDRRI also offered graduate students in land-use planning, landscape architecture, and architecture opportunities to help provide community assistance under the supervision and mentoring of faculty and practitioners. An overarching goal of the program was to help build greater rural resilience, an outcome that has received inadequate attention from academics and practitioners.